1997
DOI: 10.1108/14635789710184952
|View full text |Cite
|
Sign up to set email alerts
|

Client pressure in the commercial appraisal industry: how prevalent is it?

Abstract: Documents evidence of a loss of independence in the commercial appraisal industry in the USA. Utilizes a survey methodology to elicit the reactions of commercial appraisers to controlled scenarios of client pressure. This methodology was borrowed from established behavioural research that tested independent auditors for related independence agency issues. Results indicate significant valuation effects related to the amount of business a client brings to the appraisal firm, but no significant effect related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 5 publications
0
53
0
Order By: Relevance
“…Appraisers revealed on the postal survey/ experiment by kinnard, Lenk and Worzala (1997) that they felt pervasive client pressure and had a tendency to succumb to it especially when exerted by important clients and regardless of the size of the desired adjustment. Levy and Schuck (1999) found that both sophisticated pressure, based on the use of property and market information, and unsophisticated pressure, based on the threat of withholding fee payments or future assignments, were applied to appraisers.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…Appraisers revealed on the postal survey/ experiment by kinnard, Lenk and Worzala (1997) that they felt pervasive client pressure and had a tendency to succumb to it especially when exerted by important clients and regardless of the size of the desired adjustment. Levy and Schuck (1999) found that both sophisticated pressure, based on the use of property and market information, and unsophisticated pressure, based on the threat of withholding fee payments or future assignments, were applied to appraisers.…”
Section: Literature Review and Research Hypothesismentioning
confidence: 99%
“…The valuer understands the financial implications of withdrawn transactions to clients and at the same time seeks a long-term business relation. This potentially creates a moral hazard issue for valuers with regard to deciding on an appropriate market value estimate (Cho & Megbolugbe, 1996;Kinnard, Lenk, & Worzala, 1997). In turn, the principal's awareness of this moral hazard issue opens the door for client influence.…”
Section: Professional Autonomy In Real Estate Valuationmentioning
confidence: 99%
“…The Smolen and Hambleton (1997) were among the first to provide -anecdotal -evidence of valuation revision, as surveyed valuers stated that 82% of peer valuers would accommodate unrealistic client demands. Kinnard et al (1997) and Worzala et al (1998) compare actual value revision pressure between commercial and residential valuers and conclude that 32% of residential valuers and 41% of commercial valuers did revise their valuation estimates. Interestingly, while commercial valuers appear significantly influenced by client size in their revision decisions, residential valuers are not.…”
Section: Interpersonal Valuer Judgement Biasmentioning
confidence: 99%
“…It could be arguable then that this situation could expose the agent to various forms of influence by these principals so as to attain their whims as has been established in real estate valuation process (Amidu and Aluko, 2007;Baum et. al., 2000;Chinloy, Cho and Megbolugbe, 1997;Cho and Megbolugbe, 1996;Crosby et al, 2004;Iroham, 2007;Kinnard, Lenk and Worzala, 1997;Ogunba, 1997) Chen and Yu (2009) attempted to analyze client influence on valuation both in Taiwan and Singapore. The choice of both countries was due to their similar level of economic development as well as professionalism amongst valuers practicing in the countries.…”
Section: Introductionmentioning
confidence: 99%